Բայրոնիզմի արտացոլման դրվագներ հայ գրականության մեջ - Անահիտ Բեքարյան (ՀՀ ԳԱԱ հրատ.)
Свободолюбивые настроения, романтизм справедливой борьбы, гуманизм и оптимизм поэзии Байрона волновали умы и сердца армянских писателей. Творчество Байрона оказало большое и благотворное влияние на армянских писателей, а посему в развитии мирового байронизма армянский байронизм занимает особую нишу. Lord Byron’s freedom-oriented poetry, full of romantic strive for justice, humanism and optimism excited both the minds and hearts of Armenian writers. Armenian writers were greatly impressed by Byron’s literary activities, and within the framework of world Byronism Armenian Byronism has its unique place.
Keywords: Literature; Language and Literature